The contribution of environmental sensitivity and connectedness to nature to mental health: Does nature view count? - Wigley, Isabella L. C. Mariani; Nazzari, Sarah; Pastore, Massimiliano; Provenzi, Livio; Barello, Serena (Elsevier BV, 2025)
The increasing prevalence of mental health concerns, coupled with rapid urbanization, underscores the need for comprehensive research into the complex dynamics between human beings and their natural surroundings. The present study seeks to elucidate the individual and interactive pathways linking environmental sensitivity, connectedness to nature, and exposure to nature with mental health outcomes. Data were collected via a crosssectional survey involving a large sample of n = 807 Italian citizens. Bayesian analyses revealed that higher environmental sensitivity was associated with increased risk of reporting symptoms of stress, anxiety, and depression. Additionally, connectedness to nature mediated the relationship between environmental sensitivity and mental health problems, while nature exposure interacted with environmental sensitivity to predict levels of nature connectedness. Specifically, visual exposure to nature appears to enhance the feeling of connection to nature, particularly among highly sensitive individuals, thereby mitigating the risk of psychological distress. These findings suggest that fostering a connection with nature, particularly for those with high environmental sensitivity, may be a crucial strategy for promoting mental well-being in urban environments.